"Epistula ad Hilduinum abbatem" and the origins of the bishopric of Nin: New evidence for the Lombard monasticism in Carolingian Dalmatia? - Vedriš, Trpimir (2008)
The proposed paper aims at examining the new evidence for the activities of the Lombard monks in the Carolingian Dalmatia. Referring to the interpretation (brought forth by the art historians since 1990s) of the three-apse/altar churches as the evidence of the Ambrosian liturgy in the Croatian Principality, the author examines previously unemployed liturgical and hagiographical evidence of the possible relations between North Italy and the hinterland of Zadar in the first decades of the 9th c. Departing from the record of the liturgist and imperial envoy Amalarius of Metz of his stay in Zadar in 813, the author analyses the chosen fragments from his treaty Epistula ad Hilduinum abbatem as the possible evidence for the complex situation in which the Church of Zadar found itself after the treaty of Aachen. Asking for the possible meaning of the notion of different liturgical customs in the Epistula, the author moves forward towards positing the liturgical observations of Amalarius and his voyage to Constantinople in the broader context of the diplomatic activities of the abbots of monastery of St. Silvester in Nonantola in the first decades of the 9th c. The local hagiographical tradition of Lombard royal monastery of St. Silvester is used in the attempt to share some additional light on the obscure history of the early cult of the patron saints of the cathedral and Benedictine monastery in Nin. Local evidence is taken in consideration primarily in order to underline the important Lombard impetus in the establishment of the ecclesiastical organisation in the Croatian Principality with a focus on its early centre in Nin. As the result of the analysis of the presented evidence the author, in a form of a hypothesis, proposes strengthening the/establishing links between North Italian, Lombard monasticism and Northern Dalmatia in the period when its hinterland was incorporated in the Carolingian empire leaving region’ s ecclesiastical centre – Zadar in the territory of another Empire.